Narasi Kandang: Dari Betlehem Menuju Manusia Baru Menggagas Spiritualitas Kelahiran Baru Para Religius Menurut Lukas 2:1-7 - Yosef Masan Toron (Jurnal Alternatif Wacana Ilmiah Interkultural, 2020)
We have been recently celebrating the Christmas. The Christmas among chirstians is aways regarded as the memorial celebration of the birth of Jesus, the Messiah, as the fulfillment of the prophesy of prophets in the past. The most interesting symbols found during this moment are the cave and the shepherds. Jesus, the Messiah, has chosen the cave, the most simple place as the “locus” of His birth. This choice is really an ironic panorama. The Most High, the King of the kings has made the cave and the stable to be the “locus of revelation”, the place where the High Being reveals Himself to the world. From the beginning, the Savior introduces Himself as the Most Poor among poors. Using this image, God is going to show clearly His choice and fundamental option to human being. There’s no highway to be Savior, except to follow the stoney way on the country-side. The simple narative story of Jesus’ birth in Bethlehem remind all chirstians about the value of poverty and simplicity of our human being. We are called back to our humanity, to our own Beth-lehem, our natural roots, to be aware of our own strenghts and weaknesses as the starting-point of our journey proceeding to the fullness of our dignity and our salvation. The Christmas is not only an annual liturgical celebration but also a symbolic action, inviting us back home, making us aware of our existence as human being. Christ has chosen the poverty as the “hodos”, the best way leading all human being to the fullness of salvation.